Kualitas spermatozoa post-thawing pejantan sapi Friesian Holstein pada umur yang berbeda - Ristiani, Widya Aulia; Yunus, Muhammad; Suprayogi, Tri Wahyu; Srianto, Pudji; Mustofa, Imam; Rimayanti, Rimayanti (Universitas Airlangga, 2020)
This study aimed to determine the post-thawing spermatozoa quality of Holstein-Friesian (HF) bulls at different ages. The samples were HF frozen semen of 3, 5, and 8-years -old age group produced by the Singosari National Artificial Insemination Center. Nine samples of each group were randomly purposive sampling, thawed in 37ºC water for 15 seconds, and assessed on the percentage of viability, motility, and abnormality of spermatozoa. The obtained data were analyzed using the ANOVA method, followed by Duncan's multiple range test at a 95% confidence level. The result showed that post-thawing spermatozoa viability in 5 and 8-year-old HF bull were 67 ± 6.67%, and 78 ± 7.59, both were higher (p <0.05) compared to 62.78 ± 5.76% in HF bulls 3-yearsold group. Likewise, the motility of those bull aged 5 and 8 years (69.44 ± 6.82 and 65.00 ± 9.68%, respectively) were higher (p <0.05) compared to 55, 56 ± 5.83% in 3-year-old HF bull. Meanwhile, the percentage of post-thawing spermatozoa abnormalities in the three age groups were 4.33 ± 1.96%, 5.89 ± 1.90%, and 5.33 ± 1.41%, not significantly different (p> 0.05) respectively. It concluded that the best quality of post-thawing HF semen based on the percentage of viability, motility, and morphologic abnormality was collected from 5-8 years old bull. Nevertheless, spermatozoa from the three age goups still meet the Indonesia standard quality of frozen semen for artificial insemination.